Popular Perception of the Environmental Challenges and Benefits of Selective Waste Collection in Rondonópolis (MT) (Sustainability in Debate, 2014)
The population growth, the rural exodus, the industrialization of consumer goods, and the increaseof income generate serious problems of garbage accumulation in the cities. We intend in thisstudy to identify the perception of the population of Rondonopolis (MT) about the challenges andenvironmental benefits associated to selective collection. For this reason, was use amethodological approach, both exploratory and descriptive. In this survey, we have applied aquestionnaire with a random and representative sample of the local’s residents. The results showthat the practice of separation of recyclable solid waste in their homes is a great attitude and achange in behavior that influences the formation of conscious citizens in the direction of thepreservation of the environment. Furthermore, we did not perceived difficulties to be overcomein the implementation of selective garbage collection in this city because there is already anawareness of environmental preservation by its residents.